A novel deletion mutation in the TUSC3 gene in a consanguineous Pakistani family with autosomal recessive nonsyndromic intellectual disability - Khan, Muzammil Ahmad (BioMed Central, 2011)
BACKGROUND: Intellectual disability (ID) is a serious disorder of the central nervous system with a prevalence of 1-3% in a general population. In the past decades, the research focus has been predominantly on X-linked ID (68 loci and 19 genes for non syndromic X linked ID) while for autosomal recessive nonsyndromic ID (NSID) only 30 loci and 6 genes have been reported to date. METHODS: Genome-wide homozygosity mapping with 500 K Nsp1 array (Affymetrix), CNV analysis, PCR based breakpoint mapping and DNA sequencing was performed to explore the genetic basis of autosomal recessive nonsyndromic ID in a large Pakistani family. RESULTS: Data analysis showed linkage at 8p23 locus with common homozygous region between SNPs rs6989820 and rs2237834, spanning a region of 12.494 Mb. The subsequent CNV analysis of the data revealed a homozygous deletion of 170.673 Kb which encompassed the TUSC3 gene. CONCLUSION: We report a novel deletion mutation in TUSC3 gene which is the second gene after TRAPPC9 in which mutation has been identified in more than one family with autosomal recessive NSID. The study will aid in exploring the molecular pathway of cognition.